2006
DOI: 10.1038/sj.bmt.1705531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term outcomes after allogeneic hematopoietic stem cell transplantation from matched sibling and unrelated donors

Abstract: Long-term survivors of hematopoietic stem cell transplants remain at risk of potentially fatal complications that detract from life quality. Long-term morbidity and mortality were compared between matched recipient cohorts surviving 2 or more years and defined by donor type, HLA matched sibling donor (MSD) or volunteer unrelated donor (URD). Patients were previously entered into the prospective multicenter International Unrelated Search and Transplant Study. Thirty-nine centers provided data on 108 URD and 355… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…Furthermore, results after standard-dose conditioning and unrelated donor HCT are at least as good as sibling-HCT, and may be even better in highrisk patients. 31 Results obtained with fludarabine and 2 Gy RIC in unrelated donor transplantation showed similar results. 9 What about allo-transplantation -especially with RIC -in relapsing patients?…”
Section: Whensupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, results after standard-dose conditioning and unrelated donor HCT are at least as good as sibling-HCT, and may be even better in highrisk patients. 31 Results obtained with fludarabine and 2 Gy RIC in unrelated donor transplantation showed similar results. 9 What about allo-transplantation -especially with RIC -in relapsing patients?…”
Section: Whensupporting
confidence: 71%
“…31 When dealing with elderly patients, we are frequently confronted with frail siblings with comorbidities. A young unrelated donor may be a safer option than an old sibling with respect to stem-cell donation in such situations, and be even better for the patient with the potentially higher stem-cell count in the G-CSF-mobilized graft.…”
Section: Gvhdmentioning
confidence: 99%
“…126 Pre-HCT manipulation of donor stem cells (e.g., ex-vivo T-cell depletion) has been associated with increased risk of PTLD, with particularly elevated risks when using anti-thymocyte globulin or alemtuzumab in the preparative regimen, but no difference when using MSD or URD products. 127,128 A European Society for Blood and Marrow Transplantation (EBMT) study of donor cell leukemia after 10,489 allogeneic HCTs performed during 1975–1998 found 14 cases, of which 12 were from matched related donors and two from URD.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
“…2 Paid work is essential for an individual's identity and health, enables the person to regain a sense of normality [3][4][5] and is highly desirable from a social and economic perspective. 6 A substantial number of SCT long-term survivors report disease-and treatmentrelated problems that may last for a considerable time, with a possible negative influence on general well-being, quality of life [7][8][9][10][11][12] and participation in paid work. 13 Moreover, being in work is associated with better well being among survivors previously treated with SCT.…”
Section: Introductionmentioning
confidence: 99%